The influence of fibre stacking configurations on the indentation behaviour of pineapple leaf / glass fibre reinforced hybrid composites - Dhar Malingam, Sivakumar; Ng, Lin Feng; Subramaniam, Kathiravan; Selamat, Mohd Zulkefli; Ali, Mohd Basri; Bapokutty, Omar (Science and Technology Research Institute for Defence, 2019)
Composite materials have gained wide acceptance among industries since the past decades. They have been widely employed in a wide variety of engineering applications. In this research, the influences of fibre stacking configurations on the indentation behaviour of pineapple leaf/glass fibres reinforced polypropylene hybrid composites were investigated. The indentation behaviours of hybrid composites were then compared to non-hybrid composites. Composites were fabricated through the hot press moulding compression technique using hydraulic hot press machine. The indentation behaviours of composites were presented in terms of maximum indentation force, energy absorption and specific energy absorption. The damage mechanism of composites was also studied after the indentation test. From the findings, it was concluded that the partial incorporation of glass fibre in the composite laminates improved the indentation resistance and energy absorption. In overall, nonhybrid glass fibre reinforced composite laminates showed the highest indentation resistance and energy absorption. However, the hybrid composites with the substitution of middle glass fibre with pineapple leaf fibre had a comparable indentation resistance and energy absorption to the non-hybrid glass fibre based composites. Therefore, these results have evidenced the potential of hybrid composites to supersede non-hybrid glass fibre based composites.